Differential export taxes along the oilseeds value chain: A partial equilibrium analysis - Bouët, Antoine; Estrades, Carmen; Laborde Debucquet, David (International Food Policy Research Institute, 2012)
This research has been undertaken to understand the rationale for the implementation of decreasing export taxes along the value chain in middle-income countries, in particular in the oilseeds value chain. This paper studies the implementation of Differential Export Tax (DET) rates along value chains, in particular in the oilseeds chain (seeds/vegetable oils/biodiesel); this trade policy consists of relatively high export taxes on raw commodities and relatively low taxes on processed goods. This policy may generate public revenues and benefit final consumption by lowering domestic prices of vegetable oils and biodiesel and also promotes production at more processed stages of transformation, particularly in response to tariff escalation by importing partners. The authors first study the theoretical justification of this trade policy with a simple international trade model. It shows how implementing a tax on exports of raw agricultural commodity in a country exporting seeds and vegetable oils augments the sum of profits and final consumers’ surplus in the processing sector, of farmers’ surplus, and of public revenues. Then the authors develop a world partial equilibrium model of the oilseed value chain that illustrates these theoretical conclusions. They simulate (1) the elimination of DETs in Argentina, Indonesia, and Ukraine; (2) the elimination of import tariffs applied by the European Union (EU) and the United States on the same goods; and (3) the elimination of DETs in Argentina, Indonesia, and Ukraine and of import tariffs applied by the EU and the United States. According to the authors’ estimates, both consumers and producers throughout the world benefit from the removal of export taxes in these value chains: US$931 million and US$2.2 billion, respectively. The third scenario leads to a significant expansion of world production of all activities along the value chain, including the production of biodiesel for which world output would expand by 1 percent.